Citrate sol-gel combustion preparation and photoluminescence properties of YAG：Ce phosphors - 张乐 陆洲 朱金振 杨浩 韩朋德 陈雁 张其土 (Journal of rare earths, 2012)
Yellow-emitting YAG：Ce3＋ nanocrystalline phosphors were prepared by citrate sol-gel combustion method using citric acid as the fuel and chelating agent. The influence of mole ratio of citric acid to metallic ions （MRCM）, pH value of the solution, calcination temperature and Ce-doped concentration on the structures and properties of as-prepared powders were investigated in detail. Higher crystallinity and better luminescence performance powders were obtained at MRCM=2, pH=3 and the calcination temperature of 1200 ℃. The phosphors exhibited the charactefistc broadband visible luminescence of YAG：Ce. The optimum concentration of Ce3＋ was 1.0 tool.%, and the concentration quenching was derived from the reciprocity between electric dipole and electric quadrupole （d-q）. Especially, the pH value of the solution was a key factor to obtain a stable sol-gel system and then obtain pure and homogeneous rare earth ions doped YAG phosphors at a lower tem- perature. The Y3Al5O12：Ce0.03 phosphor with optimized synthesis-condition and composition had a similar luminescence intensity with the commercial phosphor YAG：Ce.